Suboptimal dosing of rituximab in male and female patients with DLBCL. - Pfreundschuh, M.; Muller, C.; Zeynalova, S.; Kuhnt, E.; Wiesen, M. H.; Held, G.; Rixecker, T.; Poeschel, V.; Zwick, C.; Reiser, M.; Schmitz, N.; Murawski, N. (Blood, 2014)
To determine the effect of gender on outcome, the male hazard ratio for progression-free survival (HRPFS-male) was determined in patients with diffuse large B-cell lymphoma (DLBCL). In young patients (MapThera International Trial study), HRPFS-male was 1.3 (P = .092) without and 1.1 (P = .660) with rituximab. In elderly patients (RICOVER-60 study), HRPFS-male was 1.1 (P = .348) with CHOP but increased to 1.6 (P = .004) with R-CHOP. The similar improvements of outcome in young patients were associated with similar rituximab clearances in young males and females (9.89 vs 10.38 mL/h; P = .238), whereas the greater benefit for elderly females was associated with a slower rituximab clearance (8.47 vs 10.59 mL/h; P = .005) and hence higher serum levels and longer exposure times, attributable to an age-dependent (P = .004) decrease of rituximab clearance in females but not males. Compared with elderly females, all other subgroups had significantly faster rituximab clearances and hence appear to be suboptimally dosed when rituximab is given at 375 mg/m(2). Although early results of pharmacokinetic-based prospective trials designed to exploit the full therapeutic potential of rituximab suggest that increased doses and/or prolonged exposure times can improve the outcome of elderly males with DLBCL, further studies are warranted that address the optimization of rituximab dose and schedule in all subgroups of DLBCL patients.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Monoclonal, Murine-Derived/administration & dosage/pharmacokinetics/*therapeutic use; Antineoplastic Agents/administration & dosage/pharmacokinetics/*therapeutic use; Female; Humans; Lymphoma, Large B-Cell, Diffuse/*drug therapy; Male; Middle Aged; Rituximab; Treatment Outcome; Young Adult